Implementasi Konsep Sustainable Architecture pada Pusat Pelatihan Kerajinan Batu Gunung - Franadha Zaheza Agma; Dian P. E. Laksmiyanti; Failasuf Herman Hendra (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. Tulungagung belongs to one of mountainous area which is famous for the biggest producer of mountain stone craft in East Java. Unfortunately, no institution accommodates the activity of this industry. The craftsmen of andesite stone are dominated by the predecessors as the number of young generation who wants to continue this hereditary skill is very limited. On the one hand, an industrial sector is extremely vital to improve the macro economy of Indonesia. On the other hand, this sector also contributes a lot of carbon emissions. As the rate of energy use in Indonesia is classified as high, this condition triggers architects to design an industrial facility for maximizing the potentials of climate and area to reduce the rate of energy use. Therefore, this research aimed at designing a training centre for mountain stone craft to facilitate the craftsmen. For this reason, the researcher developed a design using qualitative analysis and empiric method. Several analyses were carried out concerning the area potentials such as local regulation, land order, site condition, contour, climate, as well as social and economic aspects of user candidates. All of them were summarized into the concept of design and then accomplished by implementing the concept in the working drawing. This research yielded a design of training centre for mountain stone craft in Tulungagung supported with facilities for training site as well as production and marketing. The design actualized the theme of Sustainable Architecture to optimize the natural and site potentials through integrated waste management. Keywords: Sustainable Architecture, Training Centre, mountain stone craft. Abstrak. Tulungagung merupakan salah satu wilayah area pegunungan yang terkenal sebagai penghasil kerajinan batu gunung terbesar di Jawa Timur, namun tidak ada lembaga yang mewadahi kegiatan industri tersebut. Pengrajin batu andesit didominasi oleh para pewaris yang ahli dibidangnya karena semakin sedikit generasi muda yang meneruskan keahlian turun temurun ini. Sektor industry sangat diperlukan untuk meningkatkan ekonomi macro Negara Indonesia, di sisi lain sektor ini juga menyumbang cukup banyak emisi karbon. Laju penggunaan energi Indonesia tergolong tinggi sehingga hal ini menjadi tantangan tersendiri untuk Arsitek dalam mrancang sebuah fasilitas Industri bagaimana memaksimalkan potensi ikim dan kawasan guna menekan laju penggunaan energy. Penelitian ini bertujuan merancang pusat pelatihan kerajinan batu gunung sebagai wadah bagi pengrajin. Metode yang digunakan dalam riset ini adalah perancangan dengan analisa kualitatif dan metode desain, dimana dilakukan analisa terkait potensi kawasan seperti aturan daerah, tata guna lahan, kondisi site, kontur, iklim, aspek sosial dan ekonomi calon pengguna yang kemudian dirangkum menjadi sebuah konsep desain dan disesesaikan dengan implementasi konsep pada gambar kerja. Penelitian ini menghasilkan rancangan pusat pelatihan kerajinan batu gunung di tulungagung dengan fasilitas: tempat pelatihan, fasilitas produksi dan pemasaran. Desain ini mengusung tema Arsitektur Berkelanjutan untuk mengoptimalkan potensi alam dan site dengan manajemen limbah terpadu. Kata Kunci: Arsitektur berkelanjutan, Pusat Pelatihan, Kerajinan Batu Gunung.